2008
DOI: 10.1080/17549170801903496
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of urban form: a multidisciplinary review

Abstract: This paper characterizes and reviews multidisciplinary approaches to urban form. It begins by classifying quantitative approaches to analyzing urban form into five classes: landscape ecology, economic structure, surface transportation, community design, and urban design. It then reviews quantitative measures in each class. Based on the review, four conclusions are drawn. First, over the last two decades substantial progress has been made in the ability to measure and analyze spatial patterns that help characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
161
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(166 citation statements)
references
References 94 publications
0
161
0
5
Order By: Relevance
“…Beyond these qualitative formulations of complexity in urban form and design, how might it be measured and assessed? A stream of planning literature has considered quantitative measures of the urban form, but without explicitly engaging with complexity (e.g., Cervero and Kockelman 1997;Song and Knaap 2004;Tsai 2005;Clifton et al 2008;Ewing and Cervero 2010;Schwarz 2010;Song et al 2013b). Various complexity metrics at multiple scales, from metropolitan to neighborhood to building, are scattered throughout different bodies of literature.…”
Section: Background: Complexity Form and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond these qualitative formulations of complexity in urban form and design, how might it be measured and assessed? A stream of planning literature has considered quantitative measures of the urban form, but without explicitly engaging with complexity (e.g., Cervero and Kockelman 1997;Song and Knaap 2004;Tsai 2005;Clifton et al 2008;Ewing and Cervero 2010;Schwarz 2010;Song et al 2013b). Various complexity metrics at multiple scales, from metropolitan to neighborhood to building, are scattered throughout different bodies of literature.…”
Section: Background: Complexity Form and Designmentioning
confidence: 99%
“…Clifton et al (2008) discuss qualities of the urban form and human perceptions at multiple scales. For neighborhood and street scale urban design, perceptions of human scale are related to building heights and signage, perceptions of coherence are related to consistency of building heights, and sense of enclosure is related to building/element spacing and tree canopy.…”
Section: Visual Complexitymentioning
confidence: 99%
“…Moreover, urban design deals with the delivery of urban form, at different scales. In a metastudy of urban form, Clifton et al (2008) suggested that this is the focus of many different disciplines, which use different scales of investigation, have a different focus of interest and use different methods. We follow on from their classification of scales, and focus our review on the (sub-)metropolitan, neighborhood and pedestrian scales.…”
Section: Urban Design and City Formmentioning
confidence: 99%
“…As such, we look at urban form as shaped by urban design at three main scales: metropolitan, neighborhood and pedestrian (Clifton et al 2008;Lehrer 2010). We then search for studies that relate domains of QoL to each of these scales, including a focus on objective and subjective indicators.…”
Section: Aim and Rationale Of The Reviewmentioning
confidence: 99%
“…At its core, urban sprawl is a complex and multifaceted phenomenon with no universally accepted definition [4][5][6] and these characteristics have had a profound impact on the way that sprawl research has been conducted. The lack of a standard definition has contributed to the longevity and contentiousness of debate, while the breadth of the issue has made it difficult to study in a comprehensive manner.…”
Section: Introductionmentioning
confidence: 99%